Organizational Behavior - Robbins, Stephen P. (Pearson, 2013)
Robbins/Judge presents current, relevant research in a clear, reader-friendly writing style. Globally accepted and written by one of the most foremost authors in the field, this is a necessary read for all managers, human resource workers, and anyone needing to understand and improve their people skills.